FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT MACET PADA KOPERASI SIMPAN PINJAM SEJAHTERA (KSP) DI KOTA MATARAM - Lestari, Ni Putu Dian Ari; Sudarma, I Made; Bagiartha, I Putu Pasek (Waisya : Jurnal Ekonomi Hindu, 2023)
Cooperatives are a form of non-bank financial institutions that are already operating. One of them is a savings and loan cooperative. Savings and loan cooperative activities that provide credit to members. Borrowing from savings and loan cooperatives is faster and easier in the loan disbursement process compared to borrowing at a bank. The purpose of this study was to determine the factors that influence bad credit at the Prosperous Savings and Loans Cooperative (KSP) in the city of Mataram. The data in this study were obtained using non-participant observation methods, interviews and documentation. Data analysis techniques used data reduction, data presentation and data verification. The results of this study indicate the factors of bad credit in cooperatives that cause failures or calamities that befall members' businesses, causing cooperative members to lose their business and directly affect ongoing credit payments resulting in bad credit. Of all the problems that exist, this research provides a solution for bad credit, namely by visiting the homes of members who have bad credit so that communication does not break up between the cooperative and members who are experiencing bad credit, if it is due the credit member can pay interest on the loan before paying the loan tree.